Studies on chemical, physical and microbiological quality characteristics of Barki sheep burger fed on medicinal plants with yeast - Zaki, Engy Fayz; Ghandour, Moustafa Mohamed M.A. (International Journal of Environment, Agriculture and Biotechnology, 2023)
The current study aimed to evaluate the effect of dietary supplementation of medicinal plants with yeast on the fatty acid profile, chemical, physical and microbiological quality of Barki sheep burger during frozen storage at -20 °C for 90 days. Fifteen Barki lambs (13.46 ± 3.47 kg body weight, 4.5 months of age) were randomly divided into three groups (5 lamb/group). T1: control group fed on berseem hay and concentrate feed mixture. T2: fed on control diet + air dried powder of medicinal plants mixture which consisted of (garlic, cumin, ginger and turmeric). T3: fed as group two with (Saccharomyces cerevisiae). Results indicated that addition of yeast to medicinal plants significantly decreased (p<0.05) palmitic acid, myristic acid and increased the content of oleic acid and decatrienoic acid with non-significant effect on linoleic acid and α linolenic acid. Burger of medicinal plants with yeast group had the lowest index of atherogenicity (IA) which is healthier for human consumption. Feeding type had a slight significant effect on pH values of fresh sheep burger. No significant differences were found in shear force values of sheep burger. Cooking loss of sheep burger processed from sheep fed on medicinal plants recorded the lowest cooking loss, followed by sheep burger of medicinal plants with yeast. Burger of medicinal plants group showed the lowest TBA value. Feeding types and storage conditions significantly (p<0.05) affected on color parameters (L*, a* and b*). No significant changes in microbiological quality of sheep burger during frozen storage. In conclusion, sheep burger processed from lambs fed on diet supplemented with medicinal plants and yeast improved the composition of fatty acids, delayed the lipid oxidation and decreased the cooking loss without any negative effects on color parameters, shear force and microbial analysis which is subsequently affected on sheep burger quality and human health.